Thermoluminescence response of Ge-, Al- and Nd-doped optical fibers by 6 MeV - electron and 6 MV - photon irradiations - Hossain, I.; Saeed, M.A.; Wagiran, H.; Hida, N.; Yaakob, N.H.; Moburak, A.A. (Вопросы атомной науки и техники, 2015)
In this paper, we report the prediction of thermoluminescence responses of Neodymium-doped SiO₂ optical fibre with various dose ranges from 0.5 Gy to 4.0 Gy by 6MeV - electron irradiations without requirement for experimental measurements. A technique has been developed to calculate prediction of 6MeV - electron response of Neodymium-doped SiO₂ optical fibre by observing the measured TL response of 6MV - photon and the ratio of known measured photon/electron yield ratio distribution for Ge-doped, Al-doped optical fibre and standard TLD 100 dosimeter. The samples were kept in gelatin capsule an irradiated with 6MV - photon at the dose range from 0.5 Gy to 4.0 Gy. Siemens model Primus 3368 linear accelerator located at Hospital Sultan Ismail, Johor Bahru has been used to deliver the photon beam to the samples. We found the average response ratio of 6MV - photon and 6MeV - electron in Ge-doped, Al-doped optical fibre and standard TLD-100 dosimeter are 0.83(3). Observing the measured value of 6MV - photon irradiation this average ratio is useful to find the prediction of thermoluminescence responses by 6MeV - electron irradiation of Neodymium-doped SiO₂ optical fibre by the requirement for experimental measurements with various dose ranges from 0.5 Gy to 4.0 Gy by 6MV - photon irradiations.